Extension of Genetic Marker List Using Unnatural Amino Acid System: An Efficient Genomic Modification Strategy in Escherichia coli - Xu, Xinyi; Zhong, Huichang; Liu, Weifeng; Tao, Yong (Frontiers in Bioengineering and Biotechnology, 2020)
Genetic manipulations including chromosome engineering are essential techniques used to restructure cell metabolism. Lambda/red (λ/red) mediated recombination is the most commonly applied approach for chromosomal modulation in Escherichia coli (E. coli.). However, the efficiency of this method is significantly hampered by the laborious removal of the selectable markers. To overcome the problem, the integration helper plasmid were constructed , pSBC1a-CtR, which contains Red recombinase, Cre recombinase, and exogenous orthogonal aminoacyl-tRNA synthetase/tRNA pairs, allows an UAA to be genetically encoded at the defined site of the antibiotic resistance gene-encoded protein. The activity of this protein, as a selective mark, be lost when UAAs are not in the culture medium. Accordingly, the next procedure of antibiotic gene excising is not needed. To verify this method, poxB gene was knocked out successfully. Furthermore, sequential deletion of three target genes (galR, ptsG and pgi) was used to generate neurosporene producing strain marked by high growth rate. Thus, the site-specific incorporation unnatural amino acids (UAAs) mutagenesis system were used to control and expand the use of conditional selectable markers (CSM). And the technique is used to facilitation a rapid continuous genome editing in E. coli.